The call loan market in the U.S. financial system prior to the Federal Reserve System - Jon R. Moen; Ellis W. Tallman (Federal Reserve Bank of Atlanta, 2003)
The call loan market in New York City played a central role in funding the expansion of economic growth and capital investment in the United States in the late 1800s and early 1900s. Changes in the identity of the intermediaries providing those funds help explain why the movement for the establishment of a central bank in the United States took hold only after the panic of 1907. The growing significance of nonclearinghouse creditors to the call money market diluted the relative financial influence of the New York City bankers and compromised the apparent "coinsurance" arrangement between brokers and New York Clearinghouse lenders that prevailed during the late nineteenth century.
Keywords: 330